Model‐based approach for methoxy polyethylene glycol‐epoetin beta drug development in paediatric patients with anaemia of chronic kidney disease. Issue 4 (21st January 2020) - Chanu, Pascal; Schaefer, Franz; Warady, Bradley A.; Schmitt, Claus Peter; Reigner, Bruno; Schnetzler, Gabriel; Meyer Reigner, Sylvie; Eisner, Mark; Weichert, Arlette; Frey, Nicolas
Abstract : Aims: Methoxy polyethylene glycol‐epoetin beta (continuous erythropoietin receptor activator, C.E.R.A.) is used for the treatment of anaemia in adults with chronic kidney disease (CKD). Patients treated with shorter‐acting erythropoiesis‐stimulating agents up to three times weekly can be switched to once‐monthly C.E.R.A.. Doses can be adjusted on a monthly basis based on haemoglobin (Hb) levels during the preceding period. A model‐based approach was applied to optimise C.E.R.A. development, more specifically the confirmatory trial of the paediatric plan. Methods: Pharmacokinetic and pharmacodynamic data from a phase II paediatric study and phase II and III adult studies were analysed together using modelling and simulation to determine the pharmacokinetic/pharmacodynamic characteristics of C.E.R.A. in a broad population. Model‐based simulations of C.E.R.A. treatment outcomes in paediatric patients were performed, notably when administered subcutaneously and compared to clinical and real‐world data. Results: Age and body weight explained differences in pharmacokinetics, while the pharmacodynamic characteristics of C.E.R.A. were similar between adult and paediatric populations. Simulated Hb levels (mean and 95% prediction interval 10.9 [10.6, 11.2] g dL −1 ) and C.E.R.A. doses (median and 95% prediction interval 105 [72, 159] μg) 20 weeks after switching to subcutaneous C.E.R.A. were confirmed by observed real‐world data from International Pediatric Dialysis Network registries (mean Hb was 10.8 g dL −1 and median C.E.R.A. dose was 100 μg). Conclusions: These analyses have facilitated optimisation of the C.E.R.A. development programme in paediatric patients with anaemia of CKD to provide this patient population with faster access to the drug while avoiding unnecessary clinical trial exposure and related monitoring burden in children.